An eco-friendly pulsed magnetic field treatment on cemented carbide (WC–12Co) for enhanced milling performance. (15th March 2022) - Yang, Yongfeng; Yang, Yi; Li, QiuQin; Qin, Yuan; Yang, Gang; Zhou, Bohao; Deng, Chengjun; Wu, Mingxia
Abstract: To explore an eco-friendly way to improve the milling performance and obtain high-quality milling tools, pulsed magnetic field treatment is applied to the cemented carbide (WC–12Co) milling tools, which is a clean, rapid, and sustainable method. The effect of pulsed magnetic field treatment on the milling performance of cemented carbide tools was investigated. To evaluate the effect of this treatment technique, the milling forces, tool wear, and surface roughness were compared with those of untreated tools using polar coordinate, short-time Fourier transform, standard deviation. The results reveal that pulsed magnetic field treatment can reduce milling force ( F x is reduced by 15.90%, F y is reduced by 13.29%, F z is reduced by 47.6%), delay tool wear, and improve machined surface quality (surface roughness is decreased by 63.7%). Enhanced performance comes from the reduction of adhesive wear and the attraction of fine wear debris by the treated tool, especially, the remanence to realize the transition from two-body friction to three-body friction. In addition, the increased hardness and improved heat dissipation caused by pulsed magnetic field treatment further optimize the milling performance of the treated tool. Graphical abstract: Image 1